The impact of emotional intelligence programmes on corporate leaders within the South African retail industry - Bhengu, Raquelle (University of the Witwatersrand, Johannesburg, 2024)
This research study aims to explore the impact of emotional intelligence programmes on corporate leaders within the South African retail industry. Although previous explorative research denotes an enriching impact of programmes that train leaders about intelligence, it remains unclear whether these emotional intelligence programmes effectively teach emotional intelligence to corporate leaders who operate within the retail industry in South African. To address these gaps, a case study was conducted at one of the largest retailers in sub-Saharan Africa, examining leaders who have participated in executive emotional intelligence programmes. The research is guided by the theoretical framework of emotional intelligence, as proposed by Goleman (2009). Through in-depth interviews, data was collected for the exploration of the causal relationship observed in executive leaders after attendance of emotional intelligence learning programmes. Thematic analysis techniques were adopted where data trends and themes were scrutinised The research's primary outcomes reveal that corporate leaders' emotional intelligence experiences enhancement through emotional intelligence programmes, with the extent of improvement contingent upon organizational support and leader exposure to varying work environments. Furthermore, the findings note the necessity for continuous refresher training and periodic updates to the course content to effectively instil and perpetuate desired leadership behaviours. These insights underscore the nuanced interplay between emotional intelligence initiatives and organizational factors, providing valuable considerations for the ongoing development and sustainability of effective leadership practices
A research proposal submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2024
Keywords: Emotional Intelligence; Corporate Leadership; Human Resource Metrics; UCTD; SDG-8: Decent work and economic growth